Sistem Pendukung Keputusan Penerimaan Jurnalis Menerapkan Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) - Aldi Muharsyah; Soraya Rahma Hayati; M Ikhsan Setiawan; Heri Nurdiyanto; Yuhandri Yuhandri (STMIK Budi Darma, 2018)
Decision support systems are part of computer-based information systems (including knowledge-based systems) that are used to support decision making within an organization or company. The decision support system provides a semi-structured decision, where no one knows for sure how decisions should be made. Recruitment of employee recruitment in PT.Waspada Medan always through some tight selection before set accepted as employees at PT.Waspada Medan. There are several criteria that must be owned by each participant as a requirement to become an employee of PT.Waspada Medan. To get the best participants then the PT.Waspada Medan requires a decision support system. In this study, the authors apply Multi-Objective Optimization on the basis of Ratio Analysis (MOORA Method) as the method to be applied in the application of decision support system.